Fine‐Tuning of Molecular Packing and Energy Level through Methyl Substitution Enabling Excellent Small Molecule Acceptors for Nonfullerene Polymer Solar Cells with Efficiency up to 12.54%. Issue 9 (15th January 2018) - Luo, Zhenghui; Bin, Haijun; Liu, Tao; Zhang, Zhi‐Guo; Yang, Yankang; Zhong, Cheng; Qiu, Beibei; Li, Guanghao; Gao, Wei; Xie, Dongjun; Wu, Kailong; Sun, Yanming; et al.
Abstract: A novel small molecule acceptor MeIC with a methylated end‐capping group is developed. Compared to unmethylated counterparts (ITCPTC), MeIC exhibits a higher lowest unoccupied molecular orbital (LUMO) level value, tighter molecular packing, better crystallites quality, and stronger absorption in the range of 520–740 nm. The MeIC‐based polymer solar cells (PSCs) with J71 as donor, achieve high power conversion efficiency (PCE), up to 12.54% with a short‐circuit current ( J SC ) of 18.41 mA cm −2, significantly higher than that of the device based on J71:ITCPTC (11.63% with a J SC of 17.52 mA cm −2 ). The higher J SC of the PSC based on J71:MeIC can be attributed to more balanced μh /μe, higher charge dissociation and charge collection efficiency, better molecular packing, and more proper phase separation features as indicated by grazing incident X‐ray diffraction and resonant soft X‐ray scattering results. It is worth mentioning that the as‐cast PSCs based on MeIC also yield a high PCE of 11.26%, which is among the highest value for the as‐cast nonfullerene PSCs so far. Such a small modification that leads to so significant an improvement of the photovoltaic performance is a quite exciting finding, shining a light on the molecular design of the nonfullerene acceptors. Abstract : A novel small‐molecule acceptor MeIC with a methylated end‐capping group is developed. Compared to unmethylated counterparts (ITCPTC), MeIC exhibits higher lowest unoccupied molecular orbital (LUMO) level, tighter molecular packing, and better crystallite quality. MeIC‐based polymer solar cells with J71 as donor achieve high power conversion efficiency up to 12.54%, significantly higher than that of the device of ITCPTC.